CATALYZING PEACE THROUGH MODERATED HUMANITARIAN DIPLOMACY: THE ICRC'S HUMANITARIAN DIPLOMACY AMIDST THE ARMED CONFLICT IN AFGHANISTAN (2010-2021) - Mubin, Sayyidul (Jurnal Studi Diplomasi dan Keamanan, 2023)
Humanitarian diplomacy is an effort to protect human beings, especially in conflict areas. The armed conflict in Afghanistan that occurred caused casualties. The ICRC has been operating in Afghanistan since 1987 and has set up its headquarters there to carry out humanitarian missions. The operations carried out by the ICRC from 2001 to 2010 required evaluation and development because of the complexity of the conflict. The ICRC's humanitarian operations in 2010-2021 are different from previous years because they have intensified the protection of victims of armed conflict, the reconstruction of infrastructure, humanitarian assistance and humanitarian advocacy. This research will answer how humanitarian diplomacy was carried out by the ICRC in Afghanistan in the year of 2010-2021. This research uses Literature Reviews from books and journals regarding humanitarian diplomacy as a basis for thinking in writing with the qualitatitve method. The results of this study is that ICRC's humanitarian diplomacy in Afghanistan focuses on helping victims of armed conflict in Afghanistan and the moderated humanitarian style becomes dominant by means of humanitarian dialogue in the fields of bilateral and multilateral networks, advocacy, promotion, reconstruction and financial support, while maintaining neutrality and impartiality ICRC as a humanitarian organization. Keywords : ICRC, Humanitarian Diplomacy, Afghanistan